PMM.86 Use of Enoxaparin and Anti-factor Xa Monitoring in a Renal Obstetric Cohort. (9th June 2014) - Sarween, N; Probert, L; Webster, J; Lester, W; Day, C; Lipkin, G; Knox, E
Abstract : Introduction: Pregnant women deemed to be at high risk of thrombo-embolic disease (TED) should be treated with prophylactic low molecular weight heparin (LMWH). LMWH is cleared by the kidneys and although guidelines exist for dose reduction in patients with chronic kidney disease (CKD) these are for outside of pregnancy. LMWH activity can be monitored by measuring anti-factor Xa levels. The purpose of our study was to review the safety and efficacy of LMWH dosing and the value of anti-factor Xa levels in pregnant women with CKD. Methods: We conducted a retrospective, single centre review of pregnant women attending a tertiary renal-antenatal clinic who had received LMWH over 3 years. Results: 31 pregnancies in 28 women were identified (median age 31y (range 17–38)). LMWH was started at 3.7–34 weeks gestation (mean 11.8). Indications for treatment included proteinuria (68%) and previous VTE (26%). Prophylactic dosing was used in all but 1 case. Anti-Xa levels were always within target range in 31% of patients. Women with CKD (creatinine >70 umol/l) had higher anti-Xa levels (0.25 IU/ml vs 0.19 IU/ml, P < 0.02) and were more likely to have had a supra-therapeutic measurement (67% vs 21%, P < 0.02) compared to women with normal renal function. Delivery was by caesarean section in 73% of patients and there were no cases of significant haemorrhage or VTE. Conclusions: Prophylactic treatment with LMWH in pregnant women at high risk of VTE with CKD appears to be safe and effective. Measurement of anti-factor Xa may be helpful in guiding dosing in these patients.